Evaluating the implementation of administrative procedures at the commune-level people's committee based on the system theory: a survey in Binh Duong province - Ngo Hoai Son (Journal of State Management, 2024)
Implementing administrative procedure reform is recognized as one of the six crucial components of administrative reform in Vietnam. The study employs a systematic approach and survey methodology to assess the implementation of the current administrative procedure. The participants in the survey are civil servants responsible for carrying out administrative procedures at the commune-level government. According to the survey results, it is evident that the process factor exhibits the highest average coefficient among the three factors. The average coefficients for input factors and output factors are nearly equal. There is minimal disparity among these three factors.